Toxoplasma gondii Hsp70 as a danger signal in Toxoplasma gondii-infected mice - Mun, Hye-Seong (Cell Stress Society International, 2000)
Toxoplasma gondii Hsp70, T gondii Hsp30/bag1, and surface antigen 1 messenger RNAs were shown to be useful in analyzing stage conversion of T gondii between bradyzoites and tachyzoites. The high-level expression of T gondii Hsp70 was correlated with mortality in interferon-γ knockout mice infected with T gondii. T gondii Hsp70 inhibited the induction of nitric oxide release by peritoneal macrophages of T gondii-infected mice. These findings identify T gondii Hsp70 as a danger signal during lethal, acute T gondii infection.